Novel Antimalarial Drug Screening Based on Methyl Eugenol, Cinnamaldehyde, and Thiosemicarbazone with Cysteine Protease Inhibition: In Silico Molecular Docking, Molecular Dynamics, and ADMET Studies - Lucy Arianie; Feri Eko Hermanto; Elvina Dhiaul Iftitah; Warsito Warsito; Widodo Widodo (The Journal of Pure and Applied Chemistry Research, 2022)
Plasmodium falciparum malaria contributes to significant global diseases. Computer-aided drug design, screening, and discovery were used to analyze a novel series of Methyl Eugenol Benzaldehyde Thiosemicarbazone (MEBThi) and Methyl Eugenol Cinnamaldehyde Thiosemicarbazone (MECThi) derivatives for malaria falciparum inhibition. This present study showed that 16 molecules from 28 of MEBThi and MECThi have affinities and interaction with active-site residues of cysteine protease, a key player in erythrocyte proliferation of P. falciparum. 13-MECThi demonstrates the best binding affinity at ˗8.0 kcal/mol while co-drug ˗5.6 kcal/mol. Physicochemical and pharmacokinetic assays of 13- MECThi have also revealed this potent compound. Toxicity analysis shows that 13-MECThi does not have mutagenicity and carcinogenicity characters, whereas co-drug has mutagenicity probability. The molecular dynamic evaluation illustrated that the 13-MECThi complex has higher Root Mean Square Deviation (RMSD) values, indicating its structure was more flexible than the chloroquine complex. Root Mean Square Fluctuation (RMSF) complex of receptor and 13-MECThi has no fundamental differences with chloroquine complex. This designed compound should be considered a falciparum antimalarial drug.